Kinetic Study of Adsorption of Hexavalent Chromium in Aqueous Solution using Bay Leaf (Laurus Nobilis) as New Bio-Adsorbent - Yasin, Suhad A.; Qasim, Amin K. (Science Journal of University of Zakho, 2018)
Laurus nobilis (Bay leaf), was examined for its capacity to remove hexavalent chromium Cr(VI) poisonous, from aqueous solution. The bio-adsorbent using bay leaf obtained from Laurus nobilis was investigated in batch experiments. The influence of main parameters such as chromium concentration, pH and shaking time are tests. The effect of beginning concentration of Cr(VI) ion (10 to 50 mg/dm ), pH (1 to 6) and shaking time (5 to 180 min) have been reported. The optimum pH was found to be pH 4.. Results show that the most appropriate model was pseudo second-order kinetic and it correlate with the trial statistics well.
Keywords: Laurus nobilis; hexavalentChromium; adsorption kinetics; Waste water